Off-Label Drug Use in Oncology - E. V. Karabina; D. D. Sakaeva; O. N. Lipatov (Креативная хирургия и онкология, 2022)
The off-label use of medicines is a routine clinical practice of oncology, especially in malignant-tumour patients with no treatment alternatives left when registered-drug options have been exhausted or standard therapies reveal contraindications. The recent shift from single-gene assays to multigene panels powered by full-exome or -genome sequencing expands the capacity of precision therapy, leading to a wider agnostic off-label use of targeted drugs for detecting a particular molecular genetic disorder. Studies of the off-label drug use in oncology will clarify the feasibility and safety of such prescriptions in patients with rare forms of malignancy when registered therapies have been exhausted or standard treatment reveals contraindications. This article examines the prevalence and landscape of off-label drug use in cancer patients and elaborates on the off-label principle. The paper presents a critical reflection on the off-label use of medicines in oncology.